Derivation of predicted no-effect concentrations for thirty-five pharmaceuticals and personal care products in freshwater ecosystem - Fan, Hailin; Wang, Yuwen; Liu, Xiaojuan; Wang, Yolina Yu Lin; Kazmi, Syed Shabi Ul Hassan; Ohore, Okugbe Ebiotubo; Liu, Wenhua; Wang, Zhen (Frontiers in Marine Science, 2022)
Pharmaceuticals and personal care products (PPCPs) are contaminants of emerging concern. PPCPs have been detected in various environmental matrices which is a potential threat to the human health and environment quality. So far, there are no water quality guidelines (WQGs) established for PPCPs to protect the freshwater organisms and ecosystems. In this study, we used species sensitivity distribution (SSD) and assessment factor (AF) approaches to derive 5% hazardous concentrations (HC5s) for 35 selected PPCPs using acute and chronic toxicity information. Predicted no-effect concentration (PNECs) and acute-to-chronic ratios (ACRs) of chemicals were inherently computed to support the derivation of WQGs and ecological risk assessment. Among these, endocrine disrupting chemicals and antipsychotics posed greater threat to the freshwater environment and organisms. Highest PNEC was recorded for chloramphenicol (3620 μg/L) and lowest for fluoxetine (0.0000291 μg/L), that could have significant ecological risks. In addition, commonly used default ACR values don’ t seem to provide the adequate protection for prediction of chronic toxicity thresholds and WQGs as the highest ACR values of these drugs have reached 39100 (e.g. chloramphenicol). Findings of this study provide critical scientific information regarding the development of WQG for environmental management and risk control of PPCPs.